Postcolonial civic identity and youth (dis)organizing environment: a growth into citizenship analysis - Mohd Muzhafar Idrus,; Ruzy Suliza Hashim,; Raihanah Mohd Mydin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The fluid realities of youth in postcolonial nation-states can reflect changing and challenging landscapes. Their engagements with environment, for example, are not only elaborated in social, political, and economical contexts, but also generated through values, beliefs, and identities. This article adds to contemporary debates by positing that discussions on postcolonial civic identities have to be accompanied by youth narratives and their considerations on nature, time, and digital world(s) by taking Malaysian youths as examples. Specifically, it attempts to theorize youth civic identity within postcolonial context(s) by scrutinizing personal narratives that are symbiotically yoked with discourses on ecology and technology. Through administering personal narratives at a suburban district in West Peninsular Malaysia, this paper opens ‘windows’ into what it means for youths to participate in civic projects. Reading these narratives from the lens of growth into citizenship, their wide-ranging experiences in civic affairs can be understood in four ways, namely, recognition, responsibilities, reconciliation, and reciprocity. Two of these emerging themes, recognition and responsibilities, will be discussed in this article. Our attempt at depicting postcolonial civic identity, therefore, is part of a large-scale investigation on civic mindedness that will compel us to reflect on unofficial, continuous accounts of youth reflecting on a sense of belongingness and what the future might bring.